THE ROLE OF EQUILIBRATION IN THE FORMATION OF COGNITIVE STRUCTURES IN MATHEMATICS LEARNING - Imam Kusmaryono; Mohamad Aminudin; Kartinah Kartinah (IKIP Siliwangi and I-MES, 2022)
The purpose of this study was to investigate the critical role of equilibration in organizing and building students' cognitive structure in the practice of learning mathematics. This qualitative research was designed using a phenomenological study approach. Participants in this study were 30 high school students of XI level. The main research instrument was the interview guide format and the document of cognitive test questions with the circle equation material. Research data obtained were tested for the validity of the data by triangulation. Method triangulation was done by comparing student work data and interview data. Theory triangulation is done by comparing the descriptions of the data obtained with the relevant theoretical sources. The results showed that in the context of knowledge construction (cognitive structure), there is a strong relationship between the process of assimilation and accommodation with equilibration. The role of balance in forming cognitive structures is to guide students to organize previous knowledge (schemas) and new knowledge and create thinking structures to become more complex by considering the socio-cultural dimension (environment) in mathematics learning. Further studies suggest that when selecting topics for equilibration-based activities, teachers should provide an effective learning environment to support the formation of cognitive structures to become more prosperous and complex.